Comparison of ``What numbers make sense?'' problems solving in the Czech Republic and Lithuania - Kilienė, Ieva (Lietuvos matematikos rinkinys, 2023)
Word problems pose many challenges for students. One of them is the failure to understand the task conditions and the mechanical solution of the problem. This problem can be addressed by incorporating non-standard word problems into the learning process.  The article reviews the type of non-standard word problems called ``Where numbers make sense?'' and discusses its potential applications. It also presents the results of a study conducted with students from Lithuania and the Czech Republic.
Keywords: word problems; non-standard word problems; mathematical reasoning